2016
DOI: 10.7717/peerj.2526
|View full text |Cite
|
Sign up to set email alerts
|

Discovery pattern and species number of scale insects (Hemiptera: Coccoidea)

Abstract: Few investigations have been made of the species description trend of scale insects. The present study reports the discovery pattern and taxonomic efforts for this group based on global species and a literature dataset. In addition, three asymptotic models (Logistic, Gompertz, and Extreme Value) based on a discovery curve were used to predict the species number of scale insects. Our results showed that the species description rate has been changing over time, with certain peaks and valleys in the past 250 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Both methods concluded that two-thirds of species had been described. Similarly, several detailed taxonomic reviews of particular taxa indicated that half to three-quarters of their species were known -45-64% of soil ciliates [167]; 61-64% of micro-and macro-algae [168,169]; 65% of freshwater catfish [170]; 67% of amphibians [171]; 70% of sea anemones [172] and scale insects [173]; 75% of world flowering plants [174]; 77% of marine fish [101]; 81% of water bugs [175]; and 97% of land mammals [171]. These studies supported statistical modelling, of over 140,00 marine and 370,000 terrestrial species, that predicted 69-71% and 71-79% of species had been described, respectively [9].…”
Section: Review How Many Species May Exist?mentioning
confidence: 99%
“…Both methods concluded that two-thirds of species had been described. Similarly, several detailed taxonomic reviews of particular taxa indicated that half to three-quarters of their species were known -45-64% of soil ciliates [167]; 61-64% of micro-and macro-algae [168,169]; 65% of freshwater catfish [170]; 67% of amphibians [171]; 70% of sea anemones [172] and scale insects [173]; 75% of world flowering plants [174]; 77% of marine fish [101]; 81% of water bugs [175]; and 97% of land mammals [171]. These studies supported statistical modelling, of over 140,00 marine and 370,000 terrestrial species, that predicted 69-71% and 71-79% of species had been described, respectively [9].…”
Section: Review How Many Species May Exist?mentioning
confidence: 99%
“…Examination of the literature shows where the authors of new species descriptions work, and the increasing numbers of taxonomists in Asia, especially China, but also in South America, and no evidence of declines in other countries (Costello et al 2013b, c, d;Deng et al 2016Deng et al , 2019Liu et al 2019). This is no surprise to the public and wider scientific community because the world's scientific community has been growing for decades as economies develop.…”
Section: Discussionmentioning
confidence: 99%
“…Global scale assessments of taxa estimate that well-over half have been named: > 80% butterflies, birds and mammals, flowering plants, water bugs (Robbins and Opler 1997;Polhemus and Polhemus 2007, Bebber et al 2007Woodley et al 2009;Joppa et al 2011;Giam et al 2012;Tedesco et al 2014;Burgin et al 2018); >70% of marine fish, sea anemones, and scale insects (Eschmeyer et al 2010, Fautin et al 2013, Deng et al 2016; > 60% of micro-and macro-algae, amphibians, freshwater catfish (Guiry 2012;DeClerck et al 2013;Ota et al 2015;Giam et al 2012). Rates of new species descriptions are also declining for terrestrial and marine ectoparasites, although not for marine endoparasitic helminths (Costello 2016).…”
Section: Box 2 Progress In Discovering Speciesmentioning
confidence: 99%
“…Thailand is one of the tropical countries where fireflies are widely distributed and many species exist (Nurancha et al 2013). The insects also occur in large numbers, making it challenging to identify the correct scientific name as they have highly similar morphology which is difficult to identify in the field using the characteristic external morphology (Deng et al 2016), including firefly. In addition, damaged external characteristics or incomplete samples of field-collected specimens causes difficulties for identification (Sumruayphol et al 2016).…”
Section: Introductionmentioning
confidence: 99%